Formation of Linguocultural Competence of Uzbek High School Students in Russian Language Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is about the linguocultural content of the Uzbek language lessons, the communicative orientation of the exercises prevails at the present stage over other, traditional forms of working with language material. Armed with just such a pedagogical strategy and tactics, a modern Kyrgyz school will be able to fully solve the problems of developing productive bilingualism and polylingualism, the formation of a secondary linguistic personality in the multicultural environment of Uzbekistan. In an era of intensified integration processes, mastering several languages in a modern multicultural society is becoming the norm for almost all Uzbeks. The Uzbek language for students is the most important means of interethnic communication, a means of access to ways of mastering the values of Uzbek culture and a means of familiarization with the cultural achievements of peoples, the treasuries of world culture.